2009
DOI: 10.1007/s10484-009-9112-3
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Indices of Learning for Alpha Neurofeedback Training

Abstract: Neurofeedback has been around for decades and has applications for both clinical and healthy populations yet there is no standard method for measuring learning or a way of defining successful learning. Thus the aim of this study was to focus on alpha neurofeedback and examine changes in three different measures: amplitude, percent time, and integrated alpha, across four methods: within sessions, across sessions, within sessions compared to baseline, and across sessions compared to baseline. Participants comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 26 publications
3
62
0
Order By: Relevance
“…Beta activity did not increase in the alpha training group, indicating that the training elicited a frequency specific effect, and did not simply increase overall EEG power. The present findings add to the growing body of literature on the trainability of alpha activity in relation to relaxation (e.g., Dempster and Vernon, 2009;Egner et al, 2002;Gruzelier, 2002). These specific effects of alpha activity training on alpha activity as opposed to beta activity were evident despite a stringent control condition that included real training of random beta frequencies (Hoedlmoser et al, 2008).…”
Section: Discussionsupporting
confidence: 68%
“…Beta activity did not increase in the alpha training group, indicating that the training elicited a frequency specific effect, and did not simply increase overall EEG power. The present findings add to the growing body of literature on the trainability of alpha activity in relation to relaxation (e.g., Dempster and Vernon, 2009;Egner et al, 2002;Gruzelier, 2002). These specific effects of alpha activity training on alpha activity as opposed to beta activity were evident despite a stringent control condition that included real training of random beta frequencies (Hoedlmoser et al, 2008).…”
Section: Discussionsupporting
confidence: 68%
“…For example, Dempster and Vernon (2009) trained participants to increase alpha (8-12 Hz) over Pz. Feedback was analogue and based on the alpha amplitude above the average baseline amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…They compared amplitude, percent time, and integrated alpha as indices of learning and found that the amplitude measure was superior in showing learning across sessions both with and without baseline correction. Discussion on the appropriate index has not converged and more extensive work is needed, but such an endeavour is very time-consuming (10 weeks/participant in Dempster and Vernon, 2009). Without a measure of effect size to calculate the number of participants needed to obtain a reasonable level of statistical power, such a study could easily suffer from underpowered designs.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Dempster and Vernon (2009), who clearly outlined that the effects of alpha NF training may be better represented by changes within sessions, we were interested in the gradual increase in the EEG amplitudes across the whole course of training. As a matter of fact, the purpose of this report is to present a simple classification scheme, and should be used cautiously.…”
Section: Discussionmentioning
confidence: 99%